Relationship Between Limb Muscle Strength and Agility with Dribbling Skills in Football Extracurricular Students - Zahid Zahid; Khoirul Anwar; Fajar Hidayatullah; Septyaningrum Putri Purwoto (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This research was conducted because it wanted to know the relationship between leg muscle strength with dribbling skills and agility with dribbling skills in soccer extracurricular participants at SMP Negeri 1 Tanjung Bumi. In this study, the author uses a type of correlation research method with a quantitative approach. This research was carried out at SMP Negeri 1 Tanjung Bumi for one day from 23 to 24 March 2022. This study used 3 instruments, one of which was (1) Leg-dynamometer, this tool is used to measure leg muscle strength in kilograms (kg) ( 2) Zig-zag Run Test, this test is used to determine agility, (3) Dribbling, this test is used to determine students' dribbling skills. The sample used was a total of 30 male students who took part in extracurricular football at SMP Negeri 1 Tanjung Bumi and used the Total Sampling technique. Based on the results of the calculations and discussion above, it can be concluded that there is a relationship between leg muscle strength with dribbling skills and agility with dribbling skills in soccer extracurricular participants at SMP Negeri 1 Tanjung Bumi.